Incorporation of expanded vermiculite lightweight aggregate in cement mortar - Mo, Kim Hung; Lee, Hong Jie; Liu, Michael Yong Jing; Ling, Tung Chai (Elsevier, 2018)
This investigation presents an evaluation of the properties of cement mortars containing expanded vermiculite as partial sand replacement. When the expanded vermiculite was included at 30% and 60% replacement levels, the flow diameter was higher compared to the plain mortar without expanded vermiculite. The porous lightweight nature of the expanded vermiculite also contributed to the reduction in the unit weight and compressive strength of mortars, as well as increased water absorption. Although weight loss of the expanded vermiculite mortars subjected to elevated temperature was increased, the expanded vermiculite had positive effect in providing heat resistance and thermal stability to the mortars, observed by the reduction of compressive strength loss of mortars upon exposure to elevated temperatures.